Integrating Islamic Values in Teaching English: Lessons Learned from an Integrated Islamic School - Alfian, Alfian; Yusuf, Muhammad; Nafiah, Uyun (Universitas Lancang Kuning, 2022)
Learning English is very closely related to learning western culture, which might contrast with Islamic values, the dominant religion in Indonesia. This study finds merit in finding out the implementation of Islamic values in teaching English at an Integrated Islamic school in Indonesia, where the school chosen curriculum mandated that the subject be integrated with Islamic values since all the students are Muslim. This case study took place at an Integrated Islamic School, and the data were collected through interviewing seven English teachers and conducting a thematic analysis on their lesson plans. All the teachers admitted that integrating Islamic values in the English lesson was essential. Still, the thematic analysis showed that their perceptions about the importance of integrating Islamic values in English learning were not firmly in line with the implementation in the teaching and learning process. The teachers’ lesson plans (In Indonesian: Rencana Pelaksanaan Pembelajaran/RPP) did not depict substantial integration of Islamic values. This study recommends the practical ways of integrating Islamic that could improve teachers' understanding of Islamic values in English learning, additionally pointing out a need to develop the curriculum and teaching materials that incorporate Islamic values. This study offers novel results from the combination of teachers’ real practice and RPP analysis.